Incidental finding of aberrant mitral valve chorda during a transesophageal echocardiography evaluation for suspected endocarditis. Issue 12 (22nd August 2016) - Siddiqui, Irfan; Nguyen, Tin; Nekkanti, Rajasekhar; Movahed, Assad
Abstract : Congenital defects involving anomalous chordae of the mitral valve with attachment in the left atrium are an extremely rare finding and may result in valvular insufficiency. Few cases have been reported in the literature with multiple variations in anatomical location and insertion of aberrant chordae within the left ventricle and left atrium. Reported cases have presented with cardiovascular symptoms leading to diagnosis of anomalous mitral valve chordae. We present a case of a young female in which an aberrant mitral valve chorda was an incidental finding on transesophageal echocardiography.